Validation of the Brazilian Portuguese version of the cat-PROM5 questionnaire - Adriano Cypriano Faneli; Ricardo Danilo Chagas Oliveira; Eduardo F. Marback; Murilo Barreto Souza; Patricia F. Marback; Larrie Laporte; Cristina Muccioli (JFO Open Ophthalmology, 2025)
Objectives: Cataract surgery is the most common and effective treatment for cataract-related visual impairment, yet traditional measures of visual acuity do not fully capture patient-reported improvement in visual function. The Cat-PROM5, a five-item tool, was developed to assess cataract-related visual disability and its impact on quality of life, with validation in other languages but not in Brazilian Portuguese. This study aimed to validate the Brazilian Portuguese version of the Cat-PROM5. Methods: A cross-sectional study was conducted with 144 patients undergoing cataract surgery at a tertiary hospital in Brazil. Participants completed the Cat-PROM5 preoperatively and postoperatively to assess changes in visual function. Validation included translation and cultural adaptation following International Society for Pharmacoeconomics and Outcomes Research guidelines and Rasch analysis to evaluate psychometric properties. Main results: The Brazilian Portuguese Cat-PROM5 demonstrated satisfactory fit in Rasch modeling [χ² (5) = 4.757, p = 0.446] and reliability (Reliability = 0.813, ⍺ = 0.825, ω = 0.859). Test-retest reliability was high (r = 0.868), and correlations with Catquest-9SF and best-corrected visual acuity changes were significant. Threshold issues were observed in certain items, but unidimensionality and internal consistency were maintained. Conclusions: The Brazilian Portuguese Cat-PROM5 is a valid, reliable, and concise tool for assessing visual disability in cataract surgery patients, enabling efficient clinical assessment with high patient response rates. Its strong psychometric properties support its use in clinical and research settings for Brazilian cataract surgery patients.